Effect of environmental conditions on seed yield and metabolomic profile of camelina (Camelina sativa (L.) Crantz) through on farm multilocation trials - Clarissa Clemente; Alessandro Rossi; Luciana G. Angelini; Rocio G. Villalba; Diego A. Moreno; Francisco A. Tomás-Barberán; Silvia Tavarini (Journal of Agriculture and Food Research)
Mediterranean farmers are searching for low input and alternative crops for cropping systems diversification and for promoting innovative value chains. Since there are still limited studies on camelina to be introduced under real on-farm conditions, a multilocation trial was conducted in four different sites of inland areas of Tuscany (central Italy) with the aim of evaluating camelina productive potential and seed quality, thus defining a complete metabolomic profile. A remarkable variability has been observed on seed and oil yield, fatty acids profile and accumulation of secondary metabolites (SMs), particularly polyphenols, γ-tocopherol, and glucosinolates, highlighting how their accumulation is strongly influenced by environmental conditions. In particular, significant correlations have been found among air temperatures and SMs a accumulation, indicating that this element of weather could represent the best predictor for secondary metabolites in camelina seeds.So, this study aimed to demonstrate the interesting opportunity that camelina could represent for Mediterranean farmers, being a good source of oil, essential fatty acids, and bioactive compounds, thus representing a potential ingredient for the development of functional foods and nutraceuticals.